2021
DOI: 10.1089/fpsam.2020.0234
|View full text |Cite
|
Sign up to set email alerts
|

Case Series of Botulinum Toxin Administered to Pregnant Patients and Review of the Literature

Abstract: Objective: To evaluate a case series of patients who received medically necessary botulinum toxin during pregnancy. Materials and Methods: Retrospective chart review of three patients who underwent repeated intralaryngeal injections of botulinum toxin during pregnancy. Chart reviews were also conducted on the children to further evaluate the safety. Results: No evidence of harm to the mothers or fetuses were found in our series, including data from pregnancy and birth records using standard measures of gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A literature search of BoNT/A treatment during pregnancy (or up to 3 months prior to conception) for therapeutic or aesthetic indications, which may be inclusive of the pregnancies reported in this analysis, revealed 21 publications describing 109 women and 118 pregnancies. 18,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Some reports described other BoNT/A products, or did not specify the manufacturer, and we acknowledge the non-interchangeability of these findings. Of the published pregnancies, there was one report of a therapeutic abortion 29 and five reports of spontaneous fetal loss.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search of BoNT/A treatment during pregnancy (or up to 3 months prior to conception) for therapeutic or aesthetic indications, which may be inclusive of the pregnancies reported in this analysis, revealed 21 publications describing 109 women and 118 pregnancies. 18,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Some reports described other BoNT/A products, or did not specify the manufacturer, and we acknowledge the non-interchangeability of these findings. Of the published pregnancies, there was one report of a therapeutic abortion 29 and five reports of spontaneous fetal loss.…”
Section: Discussionmentioning
confidence: 99%
“…Another case series in 2020 reported on three patients who became pregnant while being treated with BoNT‐A for spasmodic dysphonia. All patients delivered without complications and the infants had no adverse effects from BoNT‐A treatment 86 . Newman et al report a case of a patient with cervical dystonia who was treated with abobotulinumtoxinA through 4 full‐term pregnancies without complications 87 .…”
Section: Safety Profilementioning
confidence: 99%
“…118 Similarly, a retrospective chart review demonstrated no evidence of harm to mothers or fetuses for 3 subjects who received repeated intralaryngeal ONA treatments ranging from 3 to 10 U for functional airway issues. 119…”
Section: Use In Pregnancymentioning
confidence: 99%